Sosio-Technical Factors of E-Government Implementation - Darmawan Napitupulu; Dana Indra Sensuse; Yudho Giri Sucahyo (IAES Indonesia Section, 2017)
The failure of e-Government in a number of sector units happened because the implementation of e-Government is not easy. The old paradigm assume that e-Government is simply by installing a computer makes the implementation of e-Government failure. In fact, the success of e-Government is influenced by various factors called Critical Success Factors (CSFs). This study aims to map CSFs that influenced implementation of e-Government into two term of both technology and non-technology factors. The results showed a 67 CSFs of e-Government implementation identified was successfully mapped into seven dimensions ITPOSMO (Information, Technology, Process, Objective, Staffing & Skill, Management and Other Resource).